Fluctuations of the Atlantic North Equatorial Undercurrent and Associated Changes in Oxygen Transports - Burmeister, Kristin; Luebbecke, Joke F.; Brandt, Peter; Claus, Martin; Hahn, Johannes (Geophysical Research Letters, 2020)
Abstract Although the core velocity of the Atlantic North Equatorial Undercurrent (NEUC) is low (0.1−0.3 m s−1), it has been suggested to act as an important oxygen supply route towards the oxygen minimum zone in the eastern tropical North Atlantic. For the first time, the intraseasonal to interannual NEUC variability and its impact on oxygen are investigated based on shipboard and moored velocity observations around 5°N, 23°W. In contrast to previous studies that were mainly based on models or hydrographic data, we find hardly any seasonal cycle of NEUC transports in the central Atlantic. The NEUC transport variability is instead dominated by sporadic intraseasonal events. Only some of these events are associated with high oxygen levels suggesting an occasional eastward oxygen supply by NEUC transport events. Nevertheless, they likely contribute to the local oxygen maximum in the mean shipboard section along 23°W at the NEUC core position.